1997
DOI: 10.1016/s0304-3959(96)03282-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the antiallodynic and antinociceptive efficacy of spinal morphine by antisera to dynorphin A (1–13) or MK-801 in a nerve-ligation model of peripheral neuropathy

Abstract: Neuropathic pains arising from peripheral nerve injury can result in increased sensitivity to both noxious and non-noxious stimuli and are accompanied by a number of neuroplastic alterations at the level of the spinal cord including upregulation of neurotransmitters including dynorphin, cholecystokinin and neuropeptide Y. Additionally, such pain states appear to be associated with activation of excitatory amino acid receptors including the N-methyl-D-aspartate (NMDA) receptor. Neuropathic pains have often been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 33 publications
5
47
0
Order By: Relevance
“…This result ®ts in well with results from previous studies in di erent models of neuropathic pain using either systemic (Advokat & Rhein, 1993;Kauppila et al, 1998) or intrathecal (Yamamoto & Yaksh, 1992;Ossipov et al, 1995;Nichols et al, 1997) routes of administration. In these studies, however, the NMDA receptor antagonist failed to modulate the e ect of morphine in the contralateral paw (Yamamoto & Yaksh, 1992) or in sham-operated rats (Ossipov et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result ®ts in well with results from previous studies in di erent models of neuropathic pain using either systemic (Advokat & Rhein, 1993;Kauppila et al, 1998) or intrathecal (Yamamoto & Yaksh, 1992;Ossipov et al, 1995;Nichols et al, 1997) routes of administration. In these studies, however, the NMDA receptor antagonist failed to modulate the e ect of morphine in the contralateral paw (Yamamoto & Yaksh, 1992) or in sham-operated rats (Ossipov et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that NMDA receptor antagonism reverses the ine ectiveness of morphine in depressing dorsal horn neuronal activity (Chapman & Dickenson, 1992). In addition, the sensitivity of thermal hyperalgesia (Yamamoto & Yaksh, 1992;Ossipov et al, 1995) and mechanical allodynia (Nichols et al, 1997) to intrathecal morphine can be restored by concomitant intrathecal administration of a NMDA receptor antagonist in di erent models of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that spinal glial activation following peripheral nerve injury or inflammation may be involved in altered spinal processing of sensory information (Kajander et al, 1990;Nichols et al, 1997;Aldskogius et al, 1999;Watkins et al, 2001) and the development of tactile allodynia (Jin et al, 2003;Tsuda et al, 2003). In the current study, an increase in the levels of CD11b-IR microglia and GFAP-IR astrocytes was first observed at day six days post-infusion in the dorsal horn of the spinal cord of paclitaxel-treated rats.…”
Section: Markers Indicative Of Microglia and Astrocyte Activation Arementioning
confidence: 99%
“…Animal models of neuropathic pain have shown that nerve injury induces a host of pronociceptive, neuroplastic changes, including an upregulation of dynorphin in the spinal cord, enhanced levels of cholecystokinin, increased activation of phosphorylated p38 MAP kinase, and increased content and evoked release of substance P and CGRP. [1][2][3][4]10,34,52,66,80 Upregulation of cytokine receptor mRNA in the sciatic nerve and dorsal root ganglion after partial spinal nerve ligation has been noted, and SNL has also been reported to decrease MOR density in injured peripheral axons in the ipsilateral Lamina I of dorsal horn, leading to changes in presynaptic-and postsynapticevoked responses of MOR-containing fiber. 2,46,59 These synaptic changes include a decrease in presynaptic MOR-mediated inhibition, reduced inhibition of the miniature EPSP in substantia gelatinosa neurons, a shortened afterhy-perpolarization duration in C-fibers in the L 5 dorsal root ganglion, and increased repetitive firing of Aδ-fibers during sustained depolarization.…”
mentioning
confidence: 99%